Immunohistochemical expression of the mammalian target of rapamycin pathway in penile squamous cell carcinomas: a tissue microarray study of 112 cases. Issue 6 (24th February 2014) - Chaux, Alcides; Munari, Enrico; Cubilla, Antonio L; Hicks, Jessica; Lecksell, Kristen; Burnett, Arthur L; Netto, George J
<x xml:space="preserve">Abstract</x> Aims The aim of this study was to evaluate the immunohistochemical expression of mammalian target of rapamycin (mTOR) pathway‐related biomarkers in penile carcinomas, and to assess associations with histological type, histological grade, and human papillomavirus (HPV) infection. Methods and results We built four tissue microarrays from 112 invasive penile squamous cell carcinomas, and evaluated the immunohistochemical expression of PTEN, phospho‐AKT, phospho‐mTOR, and phospho‐S6. We found decreased or loss of PTEN expression in 87% of cases. Warty and/or basaloid carcinomas had a higher proportion of PTEN loss (P = 0.02), whereas keratinizing tumours showed higher levels of phospho‐S6 (P = 0.009); phospho‐AKT and phospho‐mTOR levels were not significantly different between warty/basaloid and keratinizing carcinomas (P = 0.75 and P = 0.77, respectively). PTEN was not associated with histological grade (P = 0.18). Expression levels of phospho‐S6 were significantly higher in low‐grade tumours (P = 0.001), whereas expression levels of phospho‐AKT and phospho‐mTOR were slightly higher in high‐grade tumours (P = 0.01 and P = 0.35, respectively). We did not find any association between HPV infection and mTOR markers (P ≥ 0.2 in all cases). Conclusions Our results provide evidence of dysregulation of the mTOR pathway in penile carcinomas independently of HPV infection. Future clinical studies should further evaluate the prognostic and predictive usefulness of these markers in patients with penile cancer.